EFISIENSI EKONOMI RELATIF USAHATANI PADI SAWAH DENGAN PENDEKATAN FUNGSI KEUNTUNGAN PADA PROGRAM SEKOLAH LAPANG-PENGELOLAAN TANAMAN TERPADU (SL-PTT) DI PROVINSI BALI - Suharyanto, Suharyanto (Informatika Pertanian, 2015)
The research was conducted at three centers of rice production in the province of Bali i.e. regency of Tabanan, Gianyar and Buleleng in dry season of 2011 and wet season of 2011/2012. Data were collected through interviews using a structured questionnaire. The number of respondents consisted of 94 farmers non ICM-FFS and 122 farmers ICM-FFS with total respondents of 216 farmers. The distribution of sample respondents for each district were Tabanan district in subak Guama, Selanbawak village, Marga subdistrict as much as 78 respondents (44 ICM-FFS farmers and 34 farmer non ICM-FFS) ; Gianyar district in Subak Kumpul, Bona village, Blahbatuh subdisrict as much as 66 respondents (ICM-FFS 38 farmers and 28 farmer non ICM-FFS) and district Buleleng in subak Lebeha, Sangsit village, Sawan district as much as 72 respondent (40 farmers ICM-FFS dan 32 farmers non ICM-FFS). Relative economic efficiency and factors affecting low land rice farming profits were analyzed with Unit Output Price-Cobb Douglas Profit Function (UOP-CDPF) approach, which estimated using Ordinary Least Square (OLS). The result showed that the relative economic efficiency of ICM-FFS farmer was significantly higher than the non ICM-FFS farmers. Factors affecting low land rice farming profitability were price of N fertilizer, P fertilizer price, price of pesticides and wage of labor. The profitability of low land rice farming was higher on their own land, cultivated in the dry season and the farmers participating in the ICM-FFS.